2019
DOI: 10.1080/00051144.2019.1624409
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic virtual cluster cloud security using hybrid steganographic image authentication algorithm

Abstract: Storing data in a third party cloud system causes serious problems on data confidentiality. Generally, encryption techniques provide data confidentiality but with limited functionality, which occurs due to unsupported actions of encryption operation in cloud storage space. Hence, developing a decentralized secure storage system with multiple support functions like encryption, encoding, and forwarding tends to get complicated, when the storage system spreads. This paper aims mainly on hiding image information u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The experimental results showed that there is relative stability in the PSNR and MSE values despite the increase of hidden images within the stego image. Proposed scheme 52.31 Adaptive LSB [24] 48.21 Pixel selection technique [25] 47.53 Hybrid cluster-based [19] 4 5 Basic LSB 42.21…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental results showed that there is relative stability in the PSNR and MSE values despite the increase of hidden images within the stego image. Proposed scheme 52.31 Adaptive LSB [24] 48.21 Pixel selection technique [25] 47.53 Hybrid cluster-based [19] 4 5 Basic LSB 42.21…”
Section: Discussionmentioning
confidence: 99%
“…3 demonstrates the PSNR test of the proposed scheme in comparison with other steganography methods. It shows that the proposed solution achieves better results than some existing methods such as adaptive LSB [24], multi-stage protection using Pixel Selection [25], and hybrid cluster-based steganographic authentication algorithm [19]. The reason behind this is that small changes occur in the discrete cosine transformation coefficients.…”
Section: Msementioning
confidence: 90%
See 1 more Smart Citation